Computational fluid dynamics of computed tomography angiography to detect the hemodynamic impact of intracranial atherosclerotic stenosis. Issue 1 (December 2015) - Leng, Xinyi; Scalzo, Fabien; Fong, Albert; Johnson, Mark; Ip, Hing; Soo, Yannie; Leung, Thomas; Liu, Liping; Feldmann, Edward; Wong, Ka; Liebeskind, David
Abstract Background In symptomatic intracranial atherosclerotic stenosis (ICAS), its hemodynamic impact may affect the risk of stroke recurrence, in addition to the degree of luminal stenosis. We therefore conducted a pilot study to evaluate the feasibility to delineate the hemodynamic impact of symptomatic ICAS lesions using computational fluid dynamics (CFD) models reconstructed based on computed tomography angiography (CTA) source images. Methods Three-dimensional CFD models were reconstructed based on routine CTA source images of patients with a symptomatic ICAS lesion. The anatomic features and hemodynamic impact of target ICAS lesions were evaluated on the CFD models. The hemodynamic impact of a lesion was evaluated using distal to proximal pressure ratio (PR) and pressure gradient (PG) across the lesion. PG was defined as pressure drop across the lesion divided by length of the lesion. Results Among the 10 cases recruited, CTA source images of 9 cases were successfully processed to CFD models. The hemodynamic characteristics of the ICAS lesions could be quantitatively evaluated on the CFD models, such as the pressures, blood flow velocities, wall shear stress and shear strain rates. The median PR was 0.58 and the median PG was 93 mmHg/cm. PRs and PGs varied in cases with similar degrees of stenoses with different lesion lengths and proximal vessel diameters. Conclusions This pilot study demonstrated the feasibility to quantitatively assess the hemodynamic impact of ICAS using CFD models reconstructed based on routine CTA. Further studies are required to improve the models built in this pilot study, and to evaluate the ultimate value of this technique in clinical assessment and risk stratification of patients with symptomatic ICAS.